2020
DOI: 10.1016/j.kint.2020.04.044
|View full text |Cite
|
Sign up to set email alerts
|

A bidirectional Mendelian randomization study supports causal effects of kidney function on blood pressure

Abstract: Blood pressure and kidney function have a bidirectional relation. Hypertension has long been considered as a risk factor for kidney function decline. However, whether intensive blood pressure control could promote kidney health has been uncertain. The kidney is known to have a major role in affecting blood pressure through sodium extraction and regulating electrolyte balance. This bidirectional relation makes causal inference between these two traits difficult. Therefore, to examine the causal relations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 62 publications
3
78
0
Order By: Relevance
“…47 Some of the previously conducted MR studies showed that higher values of genetically predicted BP lead to increased risk of albuminuria 21 and hypertensive renal disease 48 but did not demonstrate a causal effect of BP on kidney function parameters. 36 This may suggest that the detected signal of causality from BP to kidney health index is driven primarily by either of these phenotypes (given that they were used to define the composite renal outcome). Most importantly however, BP does not fully account for the causal effect of both obesity measures on the kidney health index.…”
Section: Discussionmentioning
confidence: 99%
“…47 Some of the previously conducted MR studies showed that higher values of genetically predicted BP lead to increased risk of albuminuria 21 and hypertensive renal disease 48 but did not demonstrate a causal effect of BP on kidney function parameters. 36 This may suggest that the detected signal of causality from BP to kidney health index is driven primarily by either of these phenotypes (given that they were used to define the composite renal outcome). Most importantly however, BP does not fully account for the causal effect of both obesity measures on the kidney health index.…”
Section: Discussionmentioning
confidence: 99%
“…After linkage disequilibrium analysis, removing the potential confounders and fully considering the potential effect between creatinine metabolism and renal function, 35 SNP are included. The specific process has been described in the study of Yu et al 22 The 17 SNP are not found in the outcome summary data (ADPN). For the 17 SNP that could not be extracted from the outcome summary data (ADPN), the proxy SNP ( R 2 > 0.9) could be further determined, and nine SNP without the proxy SNP will not be included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Risk factors associated with CKD progression include, cardiovascular disease, age, proteinuria, acute kidney injury, hypertension, diabetes, smoking, African, African-Caribbean or Asian family origin, chronic use of nonsteroidal anti-inflammatory drugs (NSAIDs) and untreated urinary outflow tract obstruction [ 26 ]. Hypertension was considered to be on the causal pathway as it is also an outcome of worse kidney function [ 27 ]. Previous literature shows that low SES, high BMI, persistent asthma, cancer, COPD and rheumatoid arthritis are risk factors for CKD [ 28 33 ].…”
Section: Methodsmentioning
confidence: 99%